Gender Differences in Factor Scores of Anxiety and Depression among Australian University Students: Implications for Counselling Interventions - Bitsika, Vicki; Sharpley, Chris F.; Melham, Therese C. (Canadian Journal of Counselling and Psychotherapy, 2009)
Anxiety and depression inventory scores from 200 male and female university students attending a private university in Australia were examined for their factor structure. Once established, the two sets of factors were tested for gender-based differences, revealing that females were more likely than males to report symptomatology associated with pain and fatigue, sleeping and digestive problems, psychomotor agitation, confusion, and pessimism. Implications for counsellors are discussed.